Pandemic related Perceived Stress and Vaccine Hesitancy in Pakistani Adults Aged 18-59 Years - Dr. Ahmad Bilal; Sehrish Wazir; Fizzah Shahzad (Journal of Management Practices, Humanities and Social Sciences, 2021)
The current study aimed to examine the pandemic related perceived stress and vaccine hesitancy in Pakistani adults aged 18-59 years. A sample of 452 adults of Punjab, Pakistan, completed an online questionnaire using Google Forms which contained two scales, including the Oxford COVID-19 Vaccine Hesitancy Scale and Pandemic-Related Perceived Stress Scale of COVID-19. The current study aimed to predict vaccine hesitancy from perceived stress and to find demographic associations with both perceived stress and vaccine hesitancy in Pakistani adults. The results showed that the perceived stress significantly predicted vaccine hesitancy in Pakistani adults. There were found significant gender differences in both perceived stress and vaccine hesitancy. Women were found to have more perceived stress and vaccine hesitancy than men. Age had no impact on both perceived stress and vaccine hesitancy, whereas education was found to have a significant impact on perceived stress. The adults with low education were found to have more perceived stress than adults having higher education levels. It is concluded and recommended that even if an effective vaccine is prepared in the event of a pandemic, it must be properly explained to people in order to create acceptance for a vaccine. An education program that increases people's health literacy can also effectively reduce public hesitation about vaccination and improve acceptance. However, for people with high stress, other health programs should be developed to increase the positive response to the COVID-19 vaccine.